2017
DOI: 10.1007/s00277-017-3149-9
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Richter transformation of chronic lymphocytic leukemia in the era of novel therapies

Abstract: Chronic lymphocytic leukemia (CLL) has a highly variable clinical course. About 2-10% of CLL patients develop aggressive histological transformation, most commonly to diffuse large B cell lymphoma (DLBCL), historically called Richter transformation (RT). Clinical features suggestive of RT include elevated LDH and non-specific symptoms such as fever, weight loss, and lymphadenopathy. 18-fluorodeoxyglucose (18-FDG) uptake is increased on PET scan (standardized uptake value max most commonly ≥ 10). PET/CT study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 103 publications
0
38
0
Order By: Relevance
“…Interestingly, in patients with RT and prior BTKi exposure, therapy with entospletinib led to an ORR of 40.0% and median PFS of 2.9 months, while there were no responses to entospletinib in RT patients with prior PI3Kdi exposure and a median PFS of 4.6 months. Our study demonstrated encouraging responses to entospletinib in patients with R/R CLL who have failed BTK and/or PI3Kd inhibitors, especially in patients with RT, a group that has historically demonstrated a very poor prognosis [26,27]. This provides rationale for the combination use of this agent and the possibility of using this for disease control while transitioning to more definitive treatment like chimeric antigen T-cell receptor therapy and/or allogeneic hematopoietic cell transplant.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, in patients with RT and prior BTKi exposure, therapy with entospletinib led to an ORR of 40.0% and median PFS of 2.9 months, while there were no responses to entospletinib in RT patients with prior PI3Kdi exposure and a median PFS of 4.6 months. Our study demonstrated encouraging responses to entospletinib in patients with R/R CLL who have failed BTK and/or PI3Kd inhibitors, especially in patients with RT, a group that has historically demonstrated a very poor prognosis [26,27]. This provides rationale for the combination use of this agent and the possibility of using this for disease control while transitioning to more definitive treatment like chimeric antigen T-cell receptor therapy and/or allogeneic hematopoietic cell transplant.…”
Section: Discussionmentioning
confidence: 58%
“…Clinical and experimental evidence indicate that Richter syndrome cells are poorly responsive to drugs that are typically highly effective for patients with CLL, such as Ibrutinib or idelalisib (21), suggesting that novel therapeutic opportunities should be explored on the basis of the genetic and expression profile. In line with this concept, preliminary results obtained with a selective NFkB inhibitor, IT-901, confirm that these cells are, to a considerable extent, sensitive to this drug, which interrupts a critical growth circuit (22).…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of patients that developed RT are clonally related to the pre‐existent CLL phase. Molecular features associated specifically with RT include CDKN2A/B loss, TP53 disruption, NOTCH1 mutations that confer an 11‐fold increased risk of RT, CD38 expression (CD38 ≥ 30%), stereotyped B cell receptor, and unmutated IGHV status that confer a 4‐fold increased risk . Both our patients are clonally related to the pre‐existent CLL phase representing transformation from CLL.…”
Section: Discussionmentioning
confidence: 85%